A qualitative investigation into military veterans' experiences in a problem-solving court: Factors that impact graduation rates. Issue 5 (3rd September 2017) - Gallagher, John Robert; Nordberg, Anne; Gallagher, John M.
ABSTRACT: Veterans treatment courts (VTCs) are designed to offer a rehabilitative approach to criminal justice, focusing on treatment for mental health and substance use disorders. This qualitative study develops an in-depth understanding of a Midwestern VTC by asking participants ( n  = 15) their views on the most helpful aspects of the program and how the program could be more helpful. Three themes emerged from the data. 1) Military veterans felt that they were treated in a compassionate and caring manner, while also being held accountable for their behaviors. 2) Military veterans felt that they were not labeled by their mental health diagnoses, but that their identities as people and military veterans were more fully recognized. 3) Military veterans were dissatisfied with some of the services they received from the local VA. These findings are discussed in the context of problem-solving courts and military veterans' experiences of services.